A mechanistic physiologically based model to assess the effect of study design and modified physiology on formulation safe space for virtual bioequivalence of dermatological drug products - Clarke, J. F.; Thakur, K.; Polak, S. (Frontiers in Pharmacology, 2022)
Physiologically based pharmacokinetic (PBPK) models are widely accepted tools utilized to describe and predict drug pharmacokinetics (PK). This includes the use of dermal PBPK models at the regulatory level including virtual bioequivalence (VBE) studies. The current work takes the Topicort® Spray formulation containing 0.25% desoximetasone (DSM) as an example formulation. Quantitative formulation composition and IVPT data was obtained from the public literature to develop a mechanistic model using the MPML MechDermA in vitro permeation testing (IVPT) module in the Simcyp Simulator. In vitro – in vivo extrapolation functionality was used to simulate in vivo PK for various scenarios and predict a ‘safe space’ for formulation bioequivalence using the Virtual Bioequivalence (VBE) module. The potential effect of vasoconstriction, impaired barrier function and various dosing scenarios on the formulation safe space was also assessed. The model predicted ‘safe space’ for formulation solubility suggested a 50% change may cause bio-in-equivalence whereas viscosity could deviate by orders of magnitude and the formulation may still remain bioequivalent. Evaporation rate and fraction of volatile components showed some sensitivity, suggesting large changes in the volume or composition of the volatile fraction could cause bio-in-equivalence. The tested dosing scenarios showed decreased sensitivity for all formulation parameters with decreased dose. Relative formulation bioequivalence was insensitive to vasoconstriction, but the safe space became wider with decreased barrier function for all parameters, except viscosity which was unaffected.